An Investigation of Emotional Intelligence and its Association with Self-Efficacy at Higher Education Level in Pakistan - Kashan Sehrish; Kayani Sumaira; Ur Rehman Zia; Imran Muhammad; Naseerud Din Muhammad (Journal of Human Psychology, 2021)
The present study examined the effects emotional intelligence on self-Efficacy of tertiary education students. Two scales Schutte Self-Report Emotional Intelligence Scale 44 and Schwarzer & Jerusalem Self Efficacy Scale 47 were used. The pilot study was conducted to assess the reliability of the instrument and main study was conducted to assess the results on sample of the study. A sample of 50 students (25 males, 25 females) were taken from universities of Islamabad and Rawalpindi. Both questionnaire were administered to the sample. The psychometric properties of pilot study were found satisfactory. In second phase main study was conducted which considered of sample of 200 university students (100 males and 100 females). The psychometric properties of main study were also satisfactory. Scores were analysed using SPSS software. Results of demographic variables such as age, birth order, mother education, father education and number of siblings are positively correlated with both scales and sub scales. The results were significant at (p<0.05) of mean differences with gender, education and family system. This survey consists of three hypotheses, which were accepted.
Keywords: Emotional Intelligence